2019
DOI: 10.1051/matecconf/201925802008
|View full text |Cite
|
Sign up to set email alerts
|

Material quantity estimation modelling of bridge sub- substructure using regression analysis

Abstract: In construction field, a time completion and an adherence to budget are two factors that mainly influence the successful of the projects. The adherence to the budget can be achieved when the estimated budget is closed to the actual cost. For the owners, cost estimation is necessary as a guidance in determining the amount of investment. Therefore, it is very important to know the estimation of the project cost by using the limited data before the detailed plans and specifications of the project are identified. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 3 publications
0
9
0
Order By: Relevance
“…When compared to the models proposed by other authors, some significant differences of the model introduced herein can be indicated. The previous works that aimed at modeling costs of bridges in the early stages of projects were focused on cost estimates of either parts of bridge structures [2][3][4] or specific types of bridges [5][6][7][8]. The model introduced herein offers cost predictions of bridges as a whole object (the substructure and superstructure together).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…When compared to the models proposed by other authors, some significant differences of the model introduced herein can be indicated. The previous works that aimed at modeling costs of bridges in the early stages of projects were focused on cost estimates of either parts of bridge structures [2][3][4] or specific types of bridges [5][6][7][8]. The model introduced herein offers cost predictions of bridges as a whole object (the substructure and superstructure together).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, most of the previously proposed models are based either on regression analysis [2][3][4] or ANN [5]. The former requires a priori assumptions about the functional relationship binding bridge construction cost as a dependent variable with cost predictors as independent variables.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations